Adenovirus Methods and Protocols - Chillón, Miguel.; Chillón, Miguel.; Bosch, Assumpció.; Bosch, Assumpció. (Methods in Molecular Biology, 2014)
Reflecting the development of powerful new tools and high-throughput methods to analyze adenoviral particles and their interactions with host cells, the third edition of Adenovirus Methods and Protocols calls upon experts in the field to convey advances in molecular biology, genomics and proteomics, imaging, and bioinformatics.  Beginning with cryo-electron microscopy, atomic force microscopy, and mass spectrometry for a high resolution image and characterization of the virion, this detailed book then continues with capsid modifications and viral-like particles as promising alternatives to classical adenovirus vectors, and the study of adenovirus in host interactions in vitro at the cellular level as well as in vivo in animal models. Finally, the volume concludes with an extensive update of the most efficient protocols to generate, amplify, and/or purify, at small and large scale, standard human Ad5 as well as non-human, chimeric, and helper-dependent adenovirus vectors. Written in the greatly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and cutting-edge, Adenovirus Methods and Protocols, Third Edition serves as an ideal guide for scientists continuing to research this highly valuable viral tool.